2015
DOI: 10.1108/ijm-12-2013-0293
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between ICTs and HPWPs across occupations

Abstract: Purpose -The purpose of this paper is to analyze the specific relationship between information and communication technologies (ICT) and high performance work practices (HPWP) at employee level, both generally and per job category. Design/methodology/approach -Generalized ordered logit and logit models are estimated in relation to data from 31 European countries using the fourth European Working Conditions Survey. Findings -This paper reveals a generally positive association between ICT use and HPWP participati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
5

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 61 publications
0
7
0
5
Order By: Relevance
“…On the empirical side, our analyses show that most firms tend to employ mixed rather than pure forms of the organizational modes considered, that is, a mixture of specialization and multitasking or some combination of decentralized and centralized decision‐making (see, e.g., Figure ). Recent work also highlights differences in functional flexibility or decision authority at different establishments, hierarchical levels, occupations, or skill groups (see, e.g., Bayo‐Moriones et al, ; Bloom et al, ; Caroli & Van Reenen, ; Garicano & Wu, ; McElheran, ; see Dessein, Garicano, & Gertner, for theoretical work). Hence, it may be empirically valuable to examine the proposed framework on even more granular levels, for example, establishment‐, employee‐, or even task levels.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…On the empirical side, our analyses show that most firms tend to employ mixed rather than pure forms of the organizational modes considered, that is, a mixture of specialization and multitasking or some combination of decentralized and centralized decision‐making (see, e.g., Figure ). Recent work also highlights differences in functional flexibility or decision authority at different establishments, hierarchical levels, occupations, or skill groups (see, e.g., Bayo‐Moriones et al, ; Bloom et al, ; Caroli & Van Reenen, ; Garicano & Wu, ; McElheran, ; see Dessein, Garicano, & Gertner, for theoretical work). Hence, it may be empirically valuable to examine the proposed framework on even more granular levels, for example, establishment‐, employee‐, or even task levels.…”
Section: Resultsmentioning
confidence: 99%
“…3 See Ennen and Richter (2010) and Bayo-Moriones, Calleja-Blanco, and Lera-López (2015) for related assessments of the two strands; also Bloom et al (2014); see Biagi (2013) ;Brynjolfsson & Milgrom (2013) and Draca et al (2009) for overviews. 4 Garicano (2000) and Garicano and Wu (2012) (see Section 4.2 therein for an elaborate discussion) explain that expertise is organized hierarchically if problems are complex.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bresnahan, Brynjolfsson, and Hitt (2002) find a positive link between the diffusion of computer technologies and worker autonomy. Similarly, using the fourth European Working Conditions Survey, Bayo‐Moriones, Calleja‐Blanco, and Lera‐López (2015) showed that computer use is related to job autonomy, irrespective of the respondent’s occupation. Using a sample of Spanish manufacturing plants, Bayo‐Moriones, Billon, and Lera‐López (2017) showed that the association between computer use and job variety is more pronounced in high‐skilled jobs.…”
Section: Theoretical Considerationsmentioning
confidence: 95%